Chemoselective semihydrogenation of alkynes catalyzed by manganese(i)-PNP pincer complexes. Issue 12 (29th May 2020) - Garbe, Marcel; Budweg, Svenja; Papa, Veronica; Wei, Zhihong; Hornke, Helen; Bachmann, Stephan; Scalone, Michelangelo; Spannenberg, Anke; Jiao, Haijun; Junge, Kathrin; Beller, Matthias
Abstract : A first homogeneous manganese catalyzed chemoselective semihydrogenation of alkynes to Z -olefins in the presence of molecular hydrogen is described. Abstract : A general manganese catalyzed chemoselective semihydrogenation of alkynes to olefins in the presence of molecular hydrogen is described. The best results are obtained by applying the aliphatic Mn PNP pincer complex Mn- 3c which allows the transformation of various substituted internal alkynes to the respective Z -olefins under mild conditions and in high yields. Mechanistic investigations based on experiments and computations indicate the formation of the Z -isomer via an outer-sphere mechanism.